KARAKTERISASI NANOSILIKA DARI ABU TERBANG (FLY ASH) PT. BOSOWA ENERGI JENEPONTO DENGAN MENGGUNAKAN METODE ULTRASONIC - Desianti, Ika; Rahmaniah, Rahmaniah; Zelviani, Sri (Universitas Islam Negeri Alauddin Makassar, 2018)
This research aims at the process of making fly ash nanosilica using ultrasonic methods and to determine the characterization of nanosilica from fly ash. Many studies have shown that fly ash contains silica. The process of extracting silica from fly ash uses the reflux method extraction process. Meanwhile, the process of making silica nanoparticles uses ultrasonic methods. The ultrasonic method is a method for breaking particles by utilizing ultrasonic waves with a high frequency that is above 20 kHz. The resulting silica was divided into three with each different treatment, namely silica without sonication (TN), silica with sonication process for 60 minutes (N60) and for 120 minutes (N120). The silica each has a percentage of elements (%) ie 23.13%, 20.25% and 17.82%.